Molecular characterization and transcriptomic analysis of a novel polymycovirus in the fungus Talaromyces amestolkiae - Teng, Li; Chen, Sen; Hu, Zuquan; Chen, Jili; Liu, Hongmei; Zhang, Tingting (Frontiers in Microbiology, 2022)
Talaromyces amestolkiae is an important fungal species owing to its ubiquity in soils, plants, air, and food. In this study, we identified a novel six-segmented polymycovirus, Talaromyces amestolkiae polymycovirus 1 (TaPmV-1). Each of the double-stranded (ds) RNA segments of TaPmV-1 contained a single open reading frame, and the proteins encoded by dsRNA1, dsRNA2, dsRNA3, and dsRNA 5 shared significant amino acid identities of 56, 40, 47, and 43%, respectively, with the corresponding proteins of Aspergillus fumigatus polymycovirus-1(AfuPmV-1). DsRNA1, dsRNA3, and dsRNA5 of TaPmV-1 encoded an RNA-dependent RNA polymerase (RdRp), a viral methyltransferase, and a PAS-rich protein, respectively. The functions of the proteins encoded by dsRNA2, dsRNA4, and dsRNA6 have not been elucidated. Comparison of the virus-infected strain LSH3 with virus-cured strain LSHVF revealed that infection with TaPmV-l may reduce the production of red pigments and induce the clustering of fungal sclerotia. Furthermore, transcriptomic analyses demonstrated that infection with TaPmV-l downregulated the expression of transcripts related to metabolism, and may correlate with the reduced production of red pigments and clustering of sclerotia in T. amestolkiae. These results of this study provide novel insights into the mechanism of fungal gene regulation by polymycovirus infections at the transcriptome level, and this study is the first to report a novel polymycovirus of T. amestolkiae.